Future Orientation Among Children Affected by Parental HIV in China: An Exploratory Analysis of Complex Interactions - McDaniel, Heather L.; Harrison, Sayward E.; Fairchild, Amanda J.; Li, Xiaoming (Frontiers in Sociology, 2022)
We utilized an exploratory analytic approach to examine predictors of children’s future beliefs, an internal asset associated with resilience among children affected by HIV, with emphasis on complex interactions among multisystem factors. Children (N = 1221) affected by parental HIV in China reported on psychosocial functioning, as well as internal, familial, and community resilience assets. Exploratory data analysis was conducted using a binary segmentation program. Six binary splits on predictors accounted for 22.78% of the variance in future expectation, suggesting interactions between children’s perceived control of their future, loneliness, caregiver trust, and social support. Four binary splits accounted for 23.15% of the variance in future orientation, suggesting multiway interactions between control of the future, loneliness, social support, and perceived stigma. Findings suggest combinations of resilience factors are associated with children’s positive future beliefs. Implications for screening, prevention, and intervention among Chinese children affected by parental HIV are discussed.